2020
DOI: 10.1016/j.amjcard.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvment in COVID-19–Related Acute Respiratory Distress Syndrome

Abstract: The cardiac involvement in Coronavirus disease (COVID-19) is still under evaluation, especially in severe COVID-19-related Acute Respiratory Distress Syndrome (ARDS). The cardiac involvement was assessed by serial troponin levels and echocardiograms in 28 consecutive patients with COVID-19 ARDS consecutively admitted to our Intensive Care Unit from March 1 to March 31. Twenty-eight COVID-19 patients (aged 61.7 ± 10 years, males 79%). The majority was mechanically ventilated (86%) and 4 patients (14%) required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 13 publications
6
53
0
1
Order By: Relevance
“…According to available evidence [13,[15][16][17], echocardiography should be part of the clinical evaluation of patients with COVID-19 infection, especially those with moderateto-severe disease. Indeed, RV dimension and function and systolic pulmonary arterial pressure are sensitive indicators of RV afterload, an indirect marker of lung disease severity in COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to available evidence [13,[15][16][17], echocardiography should be part of the clinical evaluation of patients with COVID-19 infection, especially those with moderateto-severe disease. Indeed, RV dimension and function and systolic pulmonary arterial pressure are sensitive indicators of RV afterload, an indirect marker of lung disease severity in COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study included in 112 COVID-19 patients, Deng et al [15] reported an incidence of pulmonary hypertension of 13% but their series was constituted mainly by patients with mild COVID-19 disease. In a series of 28 patients with COVID-19 disease requiring intensive care unit (ICU) admission, by means of serial echocardiograms, we observed that systolic pulmonary arterial pressures were increased in all patients on ICU admission but significantly decreased during ICU stay [16]. In a cohort of 200 patients with mild disease, those with pulmonary hypertension had signs of more severe COVID-19-related lung disease [16] and Szekely et al [13] observed that patients with worse clinical grade had shorter pulmonary accelerating times suggesting increased RV afterload.…”
Section: What To Measurementioning
confidence: 99%
See 2 more Smart Citations
“…Investigations combining echocardiographic assessment and troponin measurements reported that serial echocardiograms (and electrocardiograms) failed to detect signs of myocarditis in patients with elevated troponin both in mild 2 and severe COVID-19 disease. 3 Ruling out coronary ischaemia, cardiologists should interpret troponin elevation in COVID-19 disease as multifactorial, 4 related to right ventricle (RV) increased intraventricular pressures (due to lung disease/RV dysfunction). A direct relationship was reported between troponin and C reactive protein.…”
Section: Integrated Clinical Role Of Echocardiography In Patients Witmentioning
confidence: 99%